97.0k views
2 votes
Y=-8x – 37
x+3y=4

Substitution method

User Lakota
by
5.2k points

2 Answers

1 vote

Answer:

x = -5, y = 3 or you can write it as (-5, 3).

Explanation:

y=-8x – 37

x+3y=4

From the second equation x = 4 - 3y, so substituting in equation 1:

y = -8(4 - 3y) - 37

y = -32 + 24y - 37

-23y = -69

y = 3

Now plug y = 3 into equation 1:

3 = -8x - 37

-8x = 40

x = -5.

User Jahson
by
5.5k points
4 votes

Answer:

(- 5, 3 )

Explanation:

Given the 2 equations

y = - 8x - 37 → (1)

x + 3y = 4 → (2)

Substitute y = - 8x - 37 into (2)

x + 3(- 8x - 37) = 4 ← distribute and simplify left side

x - 24x - 111 = 4

- 23x - 111 = 4 ( add 111 to both sides )

- 23x = 115 ( divide both sides by - 23 )

x = - 5

Substitute x = - 5 into (1) for corresponding value of y

y = - 8(- 5) - 37 = 40 - 37 = 3

Solution is (- 5, 3 )

User Nobrandheroes
by
5.6k points